Tobacco Use and Cervical Intraepithelial Neoplasia: Consumo de tabaco y Neoplasia Intraepitelial Cervical - Rojas Cisneros, Noemí (2020)
Objective: To determine the effect of tobacco consumption with the development in women of cervical intraepithelial neoplasia. Methods: A systematic review was conducted. The electronic search was carried out, using the research question: What is the association between smoking and the development of cervical intraepithelial neoplasia? whose PEO question was: Population: Women. Exposure: Tobacco use. Outcome: Cervical intraepithelial neoplasia. Articles published from January 1, 2014 to December 2019 were selected. Results: 71 articles were found, 55 being excluded because they did not meet the selection criteria, leaving 16 articles for this paper analysis. Those women who smoked tobacco had a significant association for the development of high-grade intraepithelial neoplasia (OR = 1.43, 95% CI = 1.14-1.80). Likewise, synergy was observed between severe smoking and the use of oral contraceptives, with a greater risk of grade II and III intraepithelial neoplasia (OR = 11.5; 95% CI, 1.88-70.40). Conclusion: The available evidence suggests the association between tobacco use and the development of cervical intraepithelial neoplasia, particularly high-grade cervical intraepithelial lesions.